Influence of ribs on the acoustic behaviour of piano resonant plates - MÜLLER, U. (Archives of Acoustics, 1980)
The eigenfrequencies and vibrational modes of a simply supported stiffened rectangular plate are determined by means of perturbation method. Additional eigenmodes are excited by the presence of ribs and the eigenfrequencies are shifted. A qualitative evaluation of the influence of these additionally excited modes on the sound radiated shows that under certain conditions the ribs can improve the sound radiation of a resonant plate.